Acceptance and Commitment Therapy for People Who Stutter - Beilby, Janet; Byrnes, M. (American Speech-Language-Hearing Association Inc, 2012)
In contemporary clinical allied health and medical settings, there has been a proliferation of Acceptance and Commitment Therapy (ACT) programs. These clinically effective programs have reduced comorbid anxiety, depression, and stress for individuals suffering from chronic medical and psychosocial issues. However, to date, there has been no published work examining the effectiveness of an integrated ACT program for individuals who stutter. In this review, we will provide a platform from which readers will be able to (a) appraise the literature regarding combined speech pathology and psychology therapeutic programs for people who stutter, (b) appreciate an overview of ACT in the context of stuttering disorders, and (c) understand the relevant psychosocial outcome measures that constitute therapeutic change. This unique review of ACT will distinguish the processes of self-concept, defusion, acceptance, mindfulness, values, and committed action in support for people who stutter who experience psychosocial distress. In the culmination of the review, we advance the integration of ACT into current treatments for individuals who stutter.